Certification of the amplifier-shaper-discriminator ASICs produced for the ATLAS MDT chambers at the HL-LHC. (1st October 2022) - Abovyan, S.; Danielyan, V.; Grasser, A.; Kortner, O.; Kroha, H.; Richter, R.; Simeonov, S.
Abstract: The front-end electronics of the ATLAS muon drift-tube chambers will be upgraded in the experiment's phase-II upgrade to comply with the new trigger and read-out scheme at the HL-LHC. A new amplifier shaper discriminator chip was developed in 130 nm Global Foundries technology for this upgrade. A preproduction of 7500 chips was launched in 2019 and tested in 2020. The functionality of the chips, the test set-up and test procedure and results showing a yield of 93% are presented. The certification of the preproduction was followed by the production of 80, 000 chips in fall 2020. The tests of a sample of 2949 preproduction and 1174 production chips gave a production yield > 93%.